Coordination Chemistry of Mixed-Donor Pyridine-Containing Macrocyclic Ligands: From Optical to Redox Chemosensors for Heavy Metal Ions - Alessandra Garau; Alexander J. Blake; Maria Carla Aragoni; Massimiliano Arca; Claudia Caltagirone; Francesco Demartin; Vito Lippolis; Giacomo Picci; Enrico Podda (Molecules)
2,8-Dithia-5-aza-2,6-pyridinophane (L1) has been used as a receptor unit in the construction of the conjugated redox chemosensor 5-ferrocenylmethyl-2,8-dithia-5-aza-2,6-pyridinophane (L3). In order to further explore the coordination chemistry of L1, and comparatively, that of its structural analogue 2,11-dithia-5,8-diaza-2,6-pyridinophane (L2), featuring two secondary nitrogen atoms in the macrocyclic unit, the crystal structures of the new synthesised complexes [Pb(L1)(ClO4)2]·½CH3CN, [Cu(L2)](ClO4)2·CH3CN and [Cd(L2)(NO3)]NO3 were determined by X-ray diffraction analysis. The electrochemical response of L3 towards the metal ions Cu2+, Zn2+, Cd2+, Hg2+, and Pb2+ was investigated by cyclic voltammetry (CV) in CH2Cl2/CH3CN 0.25:1 (v/v) mixture. Upon addition to L3 of increasing amounts of the aforementioned metal cations, the wave corresponding to the Fc+/Fc redox couple of the un-complexed L3 was gradually replaced by a new reversible wave at more positive potentials and corresponding to the Fc+/Fc redox couple of the complexed ligand. The maximum anodic shift of the ferrocene oxidation wave is observed in the presence of Pb2+ (230 mV), to which corresponds a reaction coupling efficiency (RCE) value as large as 7.9 × 103. The response selectivity of L3 is discussed in reference to the optical selectivity observed for conjugated chemosensors featuring L1 as receptor unit and different fluorogenic fragments as signalling units.